1995
DOI: 10.1111/j.1472-765x.1995.tb01066.x
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic degradation and dechlorination of 2–chlorophenol, 3-chlorophenol and 4-chlorophenol by a Pseudomonas pickettii strain

Abstract: A Gram-negative aerobic bacterium capable of using 2-chlorophenol (2-CP), 3-chlorophenol (3-CP) and 4-chlorophenol (4-CP) as sole carbon sources was isolated and characterized. The bacterium, designated LD1, was identified to be a Pseudomonas pickettii strain. LD1 was able to totally degrade and dechlorinate 2-CP (initial concentration: 1.51 mmol l-1), 3-CP (initial concentration: 0.57 mmol l-1) and 4-CP (initial concentration: 0.75 mmol l-1) within 30, 30 and 40 h of incubation, respectively, under growing-ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(32 citation statements)
references
References 19 publications
0
32
0
Order By: Relevance
“…Chlorophenol (CP) compounds are used widely as pesticides. They also can be formed in chlorinated water and by the breakdown of chlorinated aromatic compounds (Fava et al, 1995). Chlorinated compounds have a high degree of environmental persistence as well as water solubility.…”
Section: Biodegradation Capabilities Of Pseudomonas Pickettiimentioning
confidence: 99%
“…Chlorophenol (CP) compounds are used widely as pesticides. They also can be formed in chlorinated water and by the breakdown of chlorinated aromatic compounds (Fava et al, 1995). Chlorinated compounds have a high degree of environmental persistence as well as water solubility.…”
Section: Biodegradation Capabilities Of Pseudomonas Pickettiimentioning
confidence: 99%
“…© 1998 The Society for Applied Microbiology chlorinated phenols (Steiert and Crawford 1986 ;Li et al 1991 ;Kiyohara et al 1992 ;Wieser et al 1994 ;Fava et al 1995 ;Tomasi et al 1995 ;Bock et al 1996 ;Koh et al 1997). Under anaerobic conditions, CPs, independently from the substitution grade, are often reductively dechlorinated up to phenol in fresh water sediments and by microbial consortia under sulphate-reducing and methanogenic conditions (Zhang and Wiegel 1990 ;Häggblom and Young 1990 ;Turner Togna et al 1995) ; few pure cultures have been shown to degrade CPs anaerobically (Mohn and Kennedy 1992 ;Utkin et al 1995 ;Christiansen and Ahring 1996).…”
Section: Introductionmentioning
confidence: 99%
“…These pollutants are usually treated in activated sludge processes because many aerobic bacteria and fungi are able to use phenol as a source of carbon and energy (Rebhun and Galil 1988;Watanabe et al, 1996). Biodegradation of phenol, therefore, has long been the subject of numerous investigations (Ruiz-Rrdaz et al, 2001;Chang et al, 1998;Fava et al, 1995;Abd-El-Haleem et al, 2003;Dean-Ross, 1989;Solomon et al, 1994;Ahmed et al, 1995;Alleman et al, 1995;Collins and daugulis, 1997;Fulthorpe and Allen, 1995;Lin et al, 1990;Morris and Lester, 1994;Ryu et al, 2000;Wang et al, 1996). A typical pathway for metabolizing an aromatic compound like phenol is to dihydroxylate the benzene ring to form a catechol derivative and then to open the ring through ortho or meta oxidation.…”
mentioning
confidence: 99%